2020
DOI: 10.1016/j.ijcard.2020.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Suspected myocardial injury in patients with COVID-19: Evidence from front-line clinical observation in Wuhan, China

Abstract: Background: A novel coronavirus disease in Wuhan has caused an outbreak and become a major public health issue in China and great concern from international community. Myocarditis and myocardial injury were suspected and may even be considered as one of the leading causes for death of COVID-19 patients. Therefore, we focused on the condition of the heart, and sought to provide firsthand evidence for whether myocarditis and myocardial injury were caused by COVID-19. Methods: We enrolled patients with confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
472
2
31

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(527 citation statements)
references
References 21 publications
(21 reference statements)
22
472
2
31
Order By: Relevance
“…Ours is one of the rst studies to assess echocardiographic ndings in admitted COVID-19 patients, irrespective of severity and its relationship to several biomarkers. Previous studies have detailed cardiac injury associated with COVID-19 based on troponin levels, ECG ndings and echocardiogram features (13)(14)(15). The aetiology of cardiac dysfunction as it relates to abnormal TTE is likely to be multifactorial as shown in our study with no relation between troponin and abnormal TTE.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Ours is one of the rst studies to assess echocardiographic ndings in admitted COVID-19 patients, irrespective of severity and its relationship to several biomarkers. Previous studies have detailed cardiac injury associated with COVID-19 based on troponin levels, ECG ndings and echocardiogram features (13)(14)(15). The aetiology of cardiac dysfunction as it relates to abnormal TTE is likely to be multifactorial as shown in our study with no relation between troponin and abnormal TTE.…”
Section: Discussionmentioning
confidence: 51%
“…Some have stipulated various consequences and molecular mechanisms, nothing of which is substantial or causal (5,12). Although many studies have examined the potential of troponin I as a marker of severity, there are very few studies, to our knowledge, that have examined the echocardiography ndings in COVID-19 patients (13)(14)(15). Complicating this is the di culty of performing echocardiography at bedside whilst using personal protective equipment and the risk of infection to staff from enhanced exposure to this virus.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies reported biomarkers based on whether the patients survived or died, 20,[22][23][24][25] ve studies reported them based on whether the patient was critically ill or not. [11][12][13][14]26 Of the latter studies, 4 categorized patients as sick based on the need for ICU admission, and 1 study based it on evidence of ARDS. 21 Baseline demographics and comorbidities of patients included in the studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…There is convincing analytical and clinical data on the cardiac [4][5][6][7] and cerebral [8] involvement in patients with COVID-19. Although the incidence of thrombotic events, at least for cerebrovascular, seems to be higher than expected and their consequences are certainly very serious, the overall incidence of systemic arterial events is low, 1%.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SARS-CoV2 (Severe Acute Respiratory Syndrome Coronavirus 2) infection it has been recently emphasized that thrombotic events contribute to the severity [1] of the disease and antithrombotic treatment has been gradually scaled up worldwide [2]. An increased incidence of pulmonary embolism has been reported [3] and there is also evidence of cardiac involvement with elevated markers of myocardial damage in 10-20% of cases [4,5]. Small series of patients with coronary [6,7], cerebrovascular [8] and peripheral arterial events [9] have been reported, but their true incidence and clinical consequences are not well established.…”
Section: Introductionmentioning
confidence: 99%